Perancangan Sistem E-Learning Berbasis Web dengan Analisis SWOT pada Sekolah Menengah Umum - Putranto, Agus (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Facilities and advances in information technology such as digital library, online journal and references have not been well utilized by Regina Pacis High School. The school still implements the teacher centric teaching method where students are highly dependent on teacher that may inhibit the student’s development in independent learning. The author felt the need to propose an alternative solution to support student centric learning process by utilizing information technology advances. Therefore, an e-learning system design is made for Regina Pacis High School. To analyze the position of Regina Pacis High School the Porter's Five Forces is used. Meanwhile appropriate strategies for the school are determined using SWOT analysis. Results of Matrix IFE and Matrix EFE state that Regina Pacis High School is on the maintain-and-guard position while the results of the SWOT matrix states that the strategy of Strengths-Opportunities (SO) fits the conditions of the school. The strategies and implementation of e-learning system are expected to optimize the available technology to strengthen the position of Regina Pacis high school in the competitive market.